PENGEMBANGAN FILTER AIR DENGAN BAHAN KERAMIK UNTUK PENINGKATAN KUALITAS AIR SUNGAI - Reza Achmad Furqoni; Mahardika Prasetya Aji; Sulhadi Sulhadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Potable water will increasingly scarce with a concomitant increase in population and the natural environmental increasingly difficult to equal this basic requirement. Ironically, research development for potable water is very slow dan its look like not taken seriously. All this time, dempet river in Kabupaten Demak is one of water sources that be used by local people for daily needed. One of option that recommended by Indonesian Ministry of Health (2008) for processing household water consumption is use ceramics filter. Therefore, this research do for knowing effect the ceramics material in water filter to increase quality of potable water. Research start with measure debit and permeability of filter and measure turbidity level of water after it passes the filter. The result of this research showing water filter with ceramics in its basic material is very good for processing potable water in small scale.Keywords: Water Filter, Ceramics Material, Potable Water.